Análise histométrica do processo de reparo do reimplante dentário submetido à terapia com laser de baixa intensidade : estudo em ratos - Nogueira, Lamis Meorin [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
To investigate the influence of low intensity laser therapy (LLLT) in the repair process of dental reimplantation, 90 mice divided into 3 groups of 30 animals had the right upper incisor extracted. In group C the incisive was reimplanted without further intervention. In the groups L1 and L2, the teeth were irradiated with diode laser before, inside the socket, and after reimplantation, outside of the socket. This dose was repeated 24, 48 and 72 hours after surgery, the group L1 and 48, 96 and 144 hours in the L2 group. After periods of 7, 14 and 30 days, the animals were sacrificed for histological examination with hematoxylin and eosin and Picrosirius Red. We observed smaller values of inflammation in the periodontal ligament in the L1 group (p <0.05) at 7 days. Increased length of periodontal ligament reinserted in the L1 and L2 groups at 7 and 14 days. Greater extent normal pulp tissue was found in the groups L1 and L2 within 14 days. Greater commitment by root resorption was observed in group C at 30 days. It can be concluded that LLLT therapy had a positive influence on the repair of the periodontal ligament and the pulp tissue reimplanted tooth.

Para averiguar a influência da terapia com laser de baixa intensidade (LLLT) no processo de reparo em reimplante dentário, 90 ratos divididos em 3 grupos de 30 animais tiveram o incisivo superior direito extraído. No grupo C o incisivo foi reimplantado sem intervenção adicional. Nos grupos L1 e L2, os dentes foram irradiados com laser diodo antes, no interior do alvéolo, e logo após o reimplante, na parte externa do alvéolo. Essa dose foi repetida as 24, 48 e 72 horas pósoperatórias no grupo L1 e as 48, 96 e 144 horas no grupo L2. Após períodos de 7, 14 e 30 dias, os animais foram sacrificados para análise histológica em hematoxilina e eosina e Picrosirius Red. Observamos valores menores de inflamação no ligamento periodontal no grupo L1 (p<0,05) aos 7 dias. Maior extensão de ligamento periodontal reinserido, nos grupos L1 e L2, aos 7 e 14 dias. Maior extensão de tecido pulpar normal foi encontrada nos grupos L1 e L2 no período de 14 dias. Maior comprometimento pela reabsorção radicular foi observado no grupo C aos 30 dias. Pode-se concluir que a terapia com LLLT influiu positivamente no reparo do ligamento periodontal e tecido pulpar do dente reimplantado.
Histommetric analyisis of tooth immediate replantation repair process submited to Low Level Laser Terapy : study in rats
Keywords: Lasers em odontologia; Polpa dentária; Reimplante dentário; Ligamento periodontal; Tooth replantation